2014
DOI: 10.2147/idr.s65928
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of antibiotic de-escalation in bacteremic pneumonia

Abstract: BackgroundAntibiotic de-escalation is a potential strategy advocated to conserve the effectiveness of broad-spectrum antibiotics. The aim of this study was to examine the safety and feasibility of antibiotic de-escalation in patients admitted with bacteremic pneumonia.MethodsA retrospective chart review was done for patients with bacteremic pneumonia admitted to Northwest Texas Hospital in Amarillo, TX, USA, during 2008. Antibiotic de-escalation was defined as changing the empiric antibiotic regimen to a cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…If the incidence rises further, it may warrant use of newer and expensive antibiotics for empirical therapy to be deescalated after the sensitivity report. (20) Subjecting all the dacryocystitis samples to culture and sensitivity is certainly warranted in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…If the incidence rises further, it may warrant use of newer and expensive antibiotics for empirical therapy to be deescalated after the sensitivity report. (20) Subjecting all the dacryocystitis samples to culture and sensitivity is certainly warranted in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the current and effective treatment might not always be accessible under financial restrictions, and thus, similar DPP with a lower cost might be selected [12,30,31]. However, maintaining the empiric antibiotic regimen until the end of the treatment has also been reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…Of the most recent de-escalation studies, only one has mentioned the dose and mode of administration of the initial broadspectrum regimen, but it did not mention these data about the de-escalated antibiotics (11,(25)(26)(27). Another study mentioned that "the dose and pattern of administration were in accordance with current medical standards" (9).…”
Section: Discussionmentioning
confidence: 99%
“…The microorganisms used in this simulation study were Escherichia coli, Staphylococcus aureus, Streptococcus spp., Klebsiella pneumoniae, Haemophilus influenzae, Citrobacter freundii, Morganella morganii, and Proteus mirabilis, as these are microorganisms for which de-escalation is more commonly performed (9,11,(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%